Amifampridine phosphate (Firdapse®) is effective and safe in a phase 3 clinical trial in LEMS. Issue 5 (3rd March 2016) - Oh, Shin J; Shcherbakova, Natalya; Kostera‐Pruszczyk, Anna; Alsharabati, Mohammad; Dimachkie, Mazen; Blanco, Jose Munoz; Brannagan, Thomas; Lavrnić, Dragana; Shieh, Perry B; Vial, Christophe; Meisel, Andreas; Komoly, Samuel; et al.
Abstract: Objective: We evaluated the efficacy and safety of amifampridine phosphate (Firdapse ® ) for symptomatic treatment in Lambert‐Eaton myasthenic syndrome (LEMS). Methods: Phase 3, randomized, double‐blind, study. Patients were treated initially with amifampridine phosphate for 7–91 days, followed by randomization to continue amifampridine phosphate for 14 days or placebo (7‐day taper, 7‐day placebo). The primary efficacy endpoints were changes from baseline at day 14 in Quantitative Myasthenia Gravis and Subject Global Impression scores. Results: The coprimary efficacy end points and 1 of the secondary efficacy end points were met, showing a significant benefit of aminfampridine phosphate over placebo at Day 14. All 5 primary, secondary, and tertiary endpoints achieved statistical significance at Day 8. Amifampridine phosphate was well tolerated; the most common adverse events were oral and digital paresthesias, nausea, and headache. Conclusions: This study provides Class I evidence of efficacy of amifampridine phosphate as a symptomatic treatment for LEMS. Muscle Nerve 53 : 717–725, 2016